Collaborative requirements review - Nordin, Azlin; Zainal Abidin, Nadzurah; Hanum Mohd Zaini, Sara (International Journal of Engineering and Technology, 2018)
Requirements review is a formal review conducted to ensure that system requirements have been completely and clearly identified. In the conventional requirements review technique, reviewers are required to physically attend the review session and give their review feedback during the session. In such a situation, there are potential problems of scheduling the review session based on the availability of the reviewers and issues with having to physically attend the entire review session. Furthermore, the review session needs to be manually organized by the review leader and the outcome of the session need to be manually compiled. In some occasions, more than one sessions are required to be organized. Hence, the objectives of this project are to: (1) create means for the reviewers to perform review anytime and anywhere; (2) facilitate collaborative review session; (3) support checklist management for the review guidance; and (4) allow compilation of the review feedback to be generated.Â  As a case study, a web application for collaborative requirements review has been developed and tested. Finally, the features of the application are tested and issues are documented.Â Â